Untimely deaths in Renaissance drama : biography, history, catastrophe - Griffin, Andrew, 1978- (Toronto ; Buffalo ; London : University of Toronto Press, 2020)
"In the decades before history was institutionalized as a scholarly discipline, historical writing was practiced by poets, record keepers, lawyers, sermonizers, mythologers, and philosophers. In the welter of competing forms of historical thought, early modern drama often operated as a site in which claims about the nature of historical change could be treated in their frequently conflicting variety. To explore this field of competing forms of historical explanation, Untimely Death in Renaissance Drama focuses on the problem of narrative abruption in a selection of historically-minded early modern plays as they rely on various strategies to make sense of biography and fatality. Arguing that narrative forms fail in the face of untimely death, Andrew Griffin shows that the disruption appears as matter of trauma, making the untimely death both a point of narrative conflict and a social problem. Exploring the formula that early modern dramatists used to make sense of lives and deaths, this book draws on the wider context of the period's culture of history writing."--
Includes bibliographical references and index.
Print version record.
Keywords: English drama -- Early modern and Elizabethan, 1500-1600 -- History and criticism; English drama -- 17th century -- History and criticism; History in literature; Death in literature; Théâtre anglais -- 16e siècle -- Histoire et critique; Théâtre anglais -- 17e siècle -- Histoire et critique; Histoire dans la littérature.; Mort dans la littérature.; LITERARY CRITICISM -- Renaissance; Death in literature; English drama; English drama -- Early modern and Elizabethan; History in literature; 1500-1699; Criticism, interpretation, etc